"O que lhes oferece a voz do sistema?" : reflexos do sistema interamericano de direitos humanos na proteção dos adolescentes privados de liberdade nos estados-parte do Mercosul - Eilberg, Daniela Dora (2018)
This research seeks to define whether the Inter-American Human Rights System is a mechanism capable of promoting the protection of adolescents deprived of their liberty in the Mercosur member states. In this perspective, it pursues to understand: i) how does the decisions and recommendations of the Commission and the Inter-American Court on juvenile justice are internalized by the countries of the region; and (ii) how does fit the dynamic between the international normative scene - specifically, the American Convention on Human Rights and the UN Convention on the Rights of the Child - and the specific laws of Brazil's, Argentina, Uruguay, Paraguay and Venezuela juvenile systems. In this sense, the methodology used was bibliographic research for the theoretical construction addressed throughout the research. In the first chapter, a comparative study of the domestic legal systems of the Mercosur countries was carried out, referring to the Constitutions, Criminal Procedure Codes, Specialized Childhood and Legislation Laws and Criminal Laws. Comparative indicators have been drawn from the United Nations Convention and understood as minimum international standards for juvenile systems. The second chapter tried to conceptualize the control of conventionality as a tool to effectivate the internalization of the human rights in the countries and to verify the status conferred by the Constitutions to the international human rights treaties. So, it was done a documentary research of the Inter-American Court jurisprudence. Then, a qualitative and qualitative research was carried out on the cases of death and torture of adolescents deprived of liberty, which resulted in a case study, whose sample had the cut from 1995 to 2017 and the Mercosur region. Lastly, for the critical construction of the third chapter, semi-structured interviews were conducted with judges and lawyers of the Inter-American Court, teachers and human rights defenders specialized in childhood and youth.